The biology, behaviour and survival of pupating false codling moth, Thaumatotibia leucotreta (Meyrick) (Lepidoptera: Tortricidae), a citrus pest in South Africa - Love, Claire Natalie (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2015)
Control of the citrus pest, false codling moth (FCM), Thaumatotibia leucotreta Meyrick (Lepidoptera: Tortricidae) is crucial for the South African citrus industry. The economic losses and phytosanitary status of this pest, coupled with increased consumer awareness and demands, has created a need for effective, IPM-compatible control measures for use against the soil-dwelling life stages of FCM. Promising developments in the field of microbial control through the use of entomopathogenic fungi (EPF) and entomopathogenic nematodes (EPNs) have highlighted the need for research regarding pupation biology, behaviour and survival of FCM, as a good understanding of biology of the target organism is an important component of any biological control programme. The aim of this study was to improve the current understanding of FCM pupation habits through the manipulation of soil texture class, ground cover, shading, soil compaction, air temperature, and soil moisture in the laboratory. These findings would then be used to aid the biological control programmes using EPF and EPNs against FCM in the soil. Three soil texture classes (sandy loam, silt loam and silty clay loam) were obtained from orchards for use in the study. FCM larvae were allowed to drop into the soil of their own accord and the pupation behaviour that followed was then captured on film with pupae formed in the soil being kept in order to measure adult eclosion. In general, very few abiotic factors had a clear influence on FCM pupation. Larval wandering time and distance was short, but also variable between individuals. Distance did increase when soils were moist. Pupation depth was shallow, with pupal cocoons generally being formed on the soil surface. Depth of pupation was less than one centimetre for all abiotic conditions, with little burrowing into soil. Eclosion success was higher for sandier soils when these were dry and uncompacted, but the addition of both moisture and soil compaction increased FCM eclosion success. FCM was sensitive to desiccation when the soils were dry and temperature limits of 15 Â°C and 32 Â°C had a strongly negative impact on eclosion success. Preferences for particular abiotic conditions were limited to only certain moisture conditions when interacting with soil texture class and a preference for pupating in soil when it is available. Limited preference was found for particular soil textures despite this having a strong influence on eclosion success, but individuals did appear to pupate in close proximity to one another. Viable direct habitat manipulation for FCM control could not be identified. These results and all of the abiotic variables measured have important implications for EPF and EPN application, survival and persistence in the soil in order to improve the ability of these biological control agents to control FCM. These are discussed in each chapter.
Keywords: Cryptophlebia leucotreta -- South Africa; Cryptophlebia leucotreta -- Larvae -- Behavior; Citrus -- Diseases and pests; Citrus -- Diseases and pests -- Biological control; Biological pest control agents; Entomopathogenic fungi; Insect nematodes; Pupae